Long term trends in oral antidiabetic drug use among children and adolescents in the Netherlands. (20th May 2015) - Fazeli Farsani, S.; Souverein, P. C.; Overbeek, J. A.; van der Vorst, M. M. J.; Knibbe, C. A. J.; Herings, R. M. C.; de Boer, A.; Mantel‐Teeuwisse, A. K.
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to document long term trends in oral antidiabetic drug (OAD) use among children and adolescents in the Netherlands. Methods A population‐based cohort study was conducted using the Dutch PHARMO Database Network. All patients younger than 20 years old with at least one OAD dispensing were identified. Age‐adjusted and age‐specific incidence (1999–2011) and prevalence (1998–2011) rates of OAD use were calculated. Trends over time were assessed using joinpoint regression software. A subset of PHARMO Database Network (including community pharmacy dispensing records linked to general practitioner data (OPD‐GP database)) was used to assess indications for OADs. Results In 2011, the overall age‐adjusted incidence and prevalence rates of OAD use were 20.7/100 000 (95% CI 19.2, 22.1) person‐years (PY) and 53.8/100 000 (95% CI 51.5, 56.1) persons, respectively. The average annual percentage change (AAPC) in the overall age‐adjusted incidence rates from 1999 to 2011 was 18.9% (95% CI 4.5, 35.2). The incidence and prevalence rates of OAD use were higher among females and older age categories. The increases in rates of OAD use were mainly driven by metformin. For only 50% of the 98 patients in the OPD‐GP database, indications for OAD prescriptions were reported with type 1 diabetes (n = 20), type 2 diabetes (n = 16), and overweight/obesity (n = 10). Conclusions Incidence and prevalence rates of OAD use in children and adolescents substantially increased in the Netherlands, especially among older age categories (10–14 and 15–19 years) and females. The main indications for use of OADs were type 1 and 2 diabetes and overweight/obesity.